A dermatoglyphics of foot in the prognosis of sporting gift: differential distinctions of dermatoglyphics of foot for sportsmen and people which do not go in for sports - Serhiyenko L.P; Lyshevska V.M (Kharkov National Pedagogical University, 2013)
The features of forming of dermatoglyphics of feet are compared for sportsmen and people, which do not go in for sports. In researches took part 209 men and 198 women in age 17-19 years, which did not go in for systematic sports. The quantitative and high-quality indexes of dermatoglyphics of fingers and soles of foot were determined on a method T.D. Gladkova. It is certain that as genetic markers of propensity to the sporting gift there can be more difficult dermatoglyphics patterns (W) on the first finger and soles of feet and more considerable indexes of comb-shaped count on the first tiptoes. A dermatoglyphics of fingers and hands of hands is more informing in a prognosis high motive gift, than dermatoglyphics of feet. It can be predefined that is analysed greater amount of indexes of dermatoglyphics of hands as compared to feet. Probability of genetic prognosis is more high for girls, what for boys.